Multicultural Educational Content in The Dayak Oral Tradition - Antonius Totok Priyadi; Kristianus Kristianus; Magdalena Magdalena (STKIP Singkawang, 2023)
This research is motivated by a high enthusiasm to develop an independent learning curriculum based on local wisdom. The aim is to explore in depth the values of multicultural education in the Dayak oral tradition in Nangka village, Menjalin District, Landak Regency as well as the social and cultural values contained in the oral tradition so that the values in question are able to provide learning for the local community. Departing from the problem that the oral tradition that developed in society began to lose its existence. At present the role of oral tradition has begun to be replaced by the existence of social media which is mushrooming among the community. The question is how the oral tradition is able to provide multicultural educational values among the community, especially the people of Nangka Village. A qualitative method with an ethnopedagogical approach is the chosen research design. The results of the study found that there are multicultural values in the oral tradition that are still developing in the midst of society, namely (1) the balala' tradition, (2) the Nyangahatn tradition; (3) Mura'atn Tradition (4) Baliatn Tradition; (5) Basaru' Sumangat Tradition. The values of multicultural education implicit in this oral tradition are the values of mutual respect, mutual respect, mutual forgiveness, mutual cooperation, friendship, tolerance, tolerance, religious, and historical values.